Response of photosynthetic apparatus of two Deschampsia species with different distribution areas on abiotic stress - Taran, N.; Storozhenko, V.; Okanenko, A.; Batsmanova, L.; Svietlova, N. (Український антарктичний журнал, 2013)
Deschampsia antarctica (endemic of Antarctic region) and Deschampsia caespitosa (inhabitant of moderate climate regions) are two plant species of Poaceae. The influences of UV-B radiation and H₂O₂ on photosynthetic apparatus of these plants were studied. Deschampsia antarctica (ендемік Антарктичного регіону) і Deschampsia caespitosa (представник регіонів помірного клімату) – два види рослин родини Poaceae. Досліджували вплив УФ-В випромінювання та Н₂О₂ на фотосинтетичний апарат цих рослин. Deschampsia antarctica (эндемик Антарктического региона) и Deschampsia caespitosa (представитель регионов умеренного климата) – два вида растений семейства Poaceaе. Исследовали влияние УФ-В излучения и Н₂О₂ на фотосинтетический аппарат этих растений.